Association of Parathyroid Hormone with Obesity among Women of Reproductive Age in an Urban Locality of Dhaka, Bangladesh (Journal of Armed Forces Medical College, Bangladesh, 2026)
Background: Obesity is a major health concern worldwide. Obesity affects both metabolic and endocrine functions. Recent research suggests that there is a link between obesity and elevated levels of parathyroid hormones (PTH), a hormone that help to regulate calcium levels in the body. Higher PTH levels may contribute to various metabolic disorders, including osteoporosis. However, data on this association among Bangladeshi women are scarce.Objective: To explore the association of serum parathyroid hormone (PTH) in obese women of reproductive age in a selective urban locality of Dhaka, Bangladesh.Methods: An analytical cross-sectional study was conducted with 30 obese women (BMI>30 kg/m2) and 30 non-obese women (BMI 18.5-24.9 kg/m2). Participants were selected using a convenience sampling method and aged 25 to 50 years; post-menopausal women were excluded. All study subjects were recruited from the Urban Primary Health Care Project (UPHCP) in old Dhaka city, and study was conducted at Dhaka Medical College. Serum iPTH levels, total calcium and BMI, were measured. Statistical analysis was performed by using statistical package for social sciences (SPSS) v10.0. Data were expressed as Mean±SD, comparison between two groups were done by using Student’s unpaired ‘t’ test, Ethical clearance was taken from ethical review committee of Dhaka Medical College, data was collected in a prescribed data collection sheet.Results: Obese women had significantly higher serum iPTH levels (38±16 pg/ml) compared to non-obese women (25±3 pg/ml; p